Structural Characteristics and Functional Implications of PM2.5 Bacterial Communities During Fall in Beijing and Shanghai, China - Pan, Yuanyuan; Pan, Xianglong; Xiao, Hongwei; Xiao, Huayun (Frontiers in Microbiology, 2019)
Air pollution characterized by fine particulate matter (PM2.5) frequently has occurred in China, and has posed threats to human health. The physiochemical characteristics of airborne PM2.5 have been extensively studied, but its bacterial structures and functions have not yet been well studied. Herein, we focused on the structural characteristics and functional implications of airborne bacteria under different pollution levels in Beijing and Shanghai. The α- and β-diversities showed no obvious difference in two cities (p>0.05). The dominant phyla Proteobacteria, Firmicutes, and Actinobacteria with total abundance of over 92% were found in all PM2.5 samples. The results of weighted unifrac non-metric multidimensional scaling (NMDS) suggested that air pollution was no obviously correlated with bacterial community but dispersed disorderly. Furthermore, canonical correlation analysis (CCA) and permutation test indicated that NH4+, SO42- and wind speed were the key factors that associated with airborne bacterial community structure. Chemical components of particulate matter played more important role in structuring bacterial community than meteorological conditions based on the result of partial CCA. In addition, the annotation of metabolic pathway suggested that the predominant genus Pseudomonas was obviously correlated with disease infections. Several dominant species might contribute to organic degradation, nitrogen cycles and ice-nuclei activities in environments. Overall, this work enhanced our understanding of functions of airborne bacteria and highlighted their potential role in atmospheric chemical progresses.